DEVELOPMENT OF DYNAMIC CALIBRATION TOOL FOR FORCE TRANSDUCER USING DROP BALL TESTER BASED ON OPTICAL INTERFEROMETERS - Satria, Eko
An increase in the need for dynamic force measurement in various research and industrial applications presents new challenges for researchers. At present there is no standard method that can be used to calibrate force transducers with dynamic forces in order to accurately measure dynamic forces. Several studies have been conducted to calibrate force transducers with dynamic forces such as using sinusoidal forces produced by shaker and shock forces. However, this method has not been able to evaluate the dynamic characteristics of the calibrated force transducer so that the calibration results can only be used under certain conditions. In this research, a tool and method has been developed to calibrate the force transducer with dynamic force by evaluating the dynamic characteristics of the force transducer. Calibration is done by working on the inertia force on the force transducer to be calibrated by dropping the spherical body on the force transducer to be calibrated. The total force acting on the spherical body during the collision can be known accurately by measuring the acceleration of the spherical body using an optical interferometer. The dynamic force acting on the force transducer is the same as the impact force acting on the spherical body, so the measurement error by the force transducer can be defined as, with is the force measured by the force transducer. The total force acting on the spherical body is defined as sphere impact F ? ?M ? g ? F where M is the mass of the spherical body and impact F is the response force acting on the spherical body from calibrated force transducer.The dynamic force acting on the force transducer is the same as the impact force acting on the spherical body, so the measurement error by the force transducer can be defined as diff trans impact F ? F ? F , with trans F is the force measured by the force transducer. The dynamic characteristic of the force transducer obtained in this experiment is that the measurement error is proportional to the second order derivative of the forces measured by the force transducer with respect to time, with 2 7 1.974 10 dt dF F trans diff ? ? ? ? .This equation is then used to correct dynamic measurement errors by the force transducer. Calibration by the developed method proved to be very significant in correcting dynamic force measurement errors by force transducers with very small root mean square (RMS) errors compared to measurement results without dynamic correction. The RMS error from the measurement result by force transducer with dynamic calibration and correction using the developed method is about 1.6 N. This error is equivalent to 1% of the maximum force exerted on the force transducer which is 160 N.